Faktor-Faktor Yang Berhubungan dengan Pemilihan Tempat Persalinan di Wilayah Kerja Puskesmas Tarus - Angie Oneng Muni; Serlie K. A. Littik; Yoseph Kenjam (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Puskesmas Tarus is the only puskesmas in Kupang Regency that has always contributed to maternal death cases since 2016-2018. The number of maternal deaths at the Tarus Health Center in 2016 was 2 cases, in 2017 1 case and in 2018 1 case. The direct cause of maternal death at the Tarus Health Center in 2020 was due to heavy bleeding and preeclampsia and childbirth was carried out at home. Therefore, the decision to choose a health facility as a place of delivery is very important to help prevent the occurrence of maternal death due to 3 late (3T) which is a factor in indirectly causing maternal death. This study aims to determine the relationship between knowledge, family income, personal autonomy, culture, accessibility, and family support with the selection of a place of delivery in the Tarus Health Center Work Area in 2022. This type of research is quantitative research that is an analytical survey with a cross-sectional research design. The size of the sample in this study of 65 people was determined by the Probability Sampling technique using a simple random sampling method. The data were then analyzed using the spearman correlation rank test. The results showed that there was a relationship between the level of knowledge (ρ = 0.000), income (ρ = 0.000), personal autonomy (ρ = 0.035) and family support (ρ = 0.025) with the selection of a place of delivery in the Tarus Health Center Working Area in 2022. Health workers who handle Maternal and Child Health (MCH) are expected to be able to carry out counseling activities with print media, electronic media, as well as other websites or social media and increase the implementation of the pregnant women's class program by more involving family husbands and local village communities.